D1.5 15M Interim report - Hadjimitsis, Diofantos G.; Lysandrou, Vasiliki; Agapiou, Athos; Lasaponara, Rosa; Masini, Nicola; Schreier, Gunter (My University, 2017)
The Deliverable 1.5 is the periodic report of the project as defined by the reporting provisions of the Grant Agreement no 691936 related to “ATHENA” project (Article 20). The present document consists the Part B of the periodic technical report of the project and covers the period from 01/12/2015 to 28/02/2017 (M1-M15 of the project). The report aims to bring out all activities accomplished by the project up to date according their description in the approved and signed version of the project. Financial adequateness of all related actions according the requests for interim payment are not included here, but are to found in a separate annex, while part A is directly uploaded to the portal of the project. The deliverable is mainly focuses to the (1) Explanation of the work carried out by the beneficiaries and Overview of the progress , (2) Objectives achieved so far as these where initially defined by the partners, (3) Explanation of the various tasks and work carried per WP and (4) the impact of the “ATHENA” project both in terms of upgrading the scientific knowledge of the partner from the low-performing country (i.e. CUT) as well as any other impact to the society and economy. It should be finally noticed that details related to the various work and tasks accomplished so far can be found in the Deliverables per se.
Keywords: ATHENA project; Technical report